Chemically Induced Models of Parkinson’s Disease: History and Perspectives for the Involvement of Ferroptosis - Wen, Shuheng; Aki, Toshihiko; Unuma, Kana; Uemura, Koichi (Frontiers in Cellular Neuroscience, 2020)
Ferroptosis is a newly discovered form of necrotic cell death characterized by its dependency on iron and lipid peroxidation. Ferroptosis has attracted much attention recently in the area of neurodegeneration since the involvement of ferroptosis in Parkinson’s disease (PD), a major neurodegenerative disease, has been indicated using animal models. Although PD is associated with both genetic and environmental factors, sporadic forms of PD account for more than 90% of total PD. In accordance with the importance of environmental factors, various neurotoxins are used as chemical inducers of PD both in vivo and in vitro. In contrast to other neurodegenerative diseases such as Alzheimer’s and Huntington’s diseases (AD and HD), many of the characteristics of PD can be reproduced in vivo by the use of specific neurotoxins. Given the indication of ferroptosis in PD pathology, a number of studies have been conducted to examine whether ferroptosis plays roles in the loss of dopaminergic neurons in PD. However, there are still few reports showing an authentic form of ferroptosis in neuronal cells during exposure to the neurotoxins used as PD inducers. In this review, we summarize the history of the uses of chemicals to create PD models in vivo and in vitro. In addition, we also survey recent reports examining the possible involvement of ferroptosis in chemical models of PD.